(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
In terms of international trade value and world fruit production, citrus is the most valuable fruit crop. In India, citrus, after mango and banana, is the third major horticultural crop. In most citrus-growing regions, it is typically commercially grown as a monoculture. Therefore, any onset of this crop epidemic will lead to tremendous destruction of crops. Citrus trees, being a perennial and evergreen crop, are affected during their life cycle by a variety of biotic and abiotic factors. A viral disease affecting citrus,’ tristeza’ caused by Citrus tristeza virus (CTV) has the greatest effect worldwide among the biotic variables. More than 100 million citrus plants, with more than 400 million grafted citrus trees already at risk of CTV infection, have already been destroyed by this virus around the world. More than one million trees have been killed by this viral infection in India alone. There are multiple pathotypes of CTV, which display distinct symptoms along with symptomless strains on various citrus hosts. It is often associated with three manifestations rapid deterioration, stem pitting, and yellow seedlings. The virus is confined to phloem and the disease continues to spread to new areas, either through the dissemination of infected buds or by semi-persistent transmission by various species of aphids. Owing to numerous and regular inoculations by aphids and the fallible existence of its RNA polymerase, infected citrus plants often harbour a large number of distinct CTV strains. As such, knowledge of the genetic diversity and geographical distribution of CTV plays a crucial role in the understanding of virus epidemiology, contributing to the proper diagnosis and development of long-term management strategies.